Republic of Tajikistan : 2009 Article IV Consultation, Final Review Under the Staff-Monitored Program, and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Tajikistan. (IMF Staff Country Reports; Country Report, 2009)
Tajikistan's growth potential is constrained by government interference in markets, and poor energy and transport infrastructure. The report focuses on Tajikistan's combined 2009 Article IV Consultation, final review under the Staff-Monitored Program, and request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility. Macroeconomic policies may need to be tightened further if external developments turn out worse than currently projected. Alternatively, additional donor support could ease the domestic adjustment burden.